THE FORMATION OF SMM STRATEGY TO GATHER MARKETING INFORMATION ON B2B MARKET - Vitaly Zhuravel; Ilona Pronina (Вестник Северо-Кавказского федерального университета)
Analysis of the use of SMM - marketing technology information environment with the use of social networks. Developed research-based recommendations for the use of funds and methods of SMM in the formation of the marketing information on the B2B market in the Internet.